2013
DOI: 10.3109/17435390.2013.829877
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and bio-accumulation of inhaled cerium oxide nanoparticles in CD1 mice

Abstract: Male CD1 mice were subjected to nose-inhalation exposure of CeO2 nanoparticles (NPs) for 0, 7, 14 or 28 days with 14 or 28 days of recovery time at an aerosol concentration of 2 mg/m(3). Markers of lung injury and pro-inflammatory cytokines (interleukin-1beta, tumour necrosis factor-alpha, interleukin-6 and macrophage inflammatory protein-2) in bronchoalveolar lavage fluid (BALF), oxidative stress in lungs, bio-accumulation, and histopathology of pulmonary and extrapulmonary tissues were assessed. BALF analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
97
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 62 publications
17
97
2
Order By: Relevance
“…The data from the study demonstrated that repeated inhalation exposure to these CeO 2 NMs resulted in significant translocation and accumulation of materials in the extra-pulmonary organs with degenerative changes in the liver and the kidneys. Additionally it was shown that the NMs are relatively difficult to clear and have the potential for some long-term toxicological effects (Aalapati et al 2014).…”
Section: Inhalation Exposurementioning
confidence: 99%
“…The data from the study demonstrated that repeated inhalation exposure to these CeO 2 NMs resulted in significant translocation and accumulation of materials in the extra-pulmonary organs with degenerative changes in the liver and the kidneys. Additionally it was shown that the NMs are relatively difficult to clear and have the potential for some long-term toxicological effects (Aalapati et al 2014).…”
Section: Inhalation Exposurementioning
confidence: 99%
“…In an inhalation study in mice, exposure of nanoceria (15 to 30 nm primary diameter and 30 to 50 m 2 /g specific surface area [SSA]) for 0, 7, 14, or 28 days at an aerosol concentration of 2 mg/m 3 resulted in significant bioaccumulation in pulmonary and extrapulmonary tissues, even 30 days after inhalation exposure 59 . Despite the small primary diameter, the test aerosol was characterized by a MMAD of 1.4 µm and a wide distribution, as indicated by a geometric standard deviation of 2.4.…”
Section: Pulmonary Deposition and Responsementioning
confidence: 99%
“…If particles were found in extra-pulmonary 1642 tissues at all, they were mainly restricted to the liver (but also 1643 occurred to minimal extents in other organs, including the brain). 1644 For CeO 2 nanoparticles, a 28-day inhalation study using male mice 1645 provided evidence of nephrotoxicity (Aalapati et al, 2014), a 1646 finding that, however, was not observed in any studies using rats 1647 (Moreno-Horn and Gebel, 2014). Also for silver nanoparticles, sys-1648 temic translocation was low, as assessed in a sub-chronic inhala-1649 tion study with rats, in spite of its higher bioavailability than the 1650 poorly soluble TiO 2 or CeO 2 nanoparticles (Moreno-Horn and 1651 Gebel, 2014).…”
mentioning
confidence: 99%